Transmural Migration of a Gossypiboma in a Bitch - Rare Cause of Intestinal Obstruction and Granulomatous Peritonitis - Kim, Seoneun; Chang, Dongwoo; Lee, Namsoon (Acta Scientiae Veterinariae, 2025)
Background: Gossypiboma is a mass of cotton that remains in the body cavity after a surgical procedure. There are numerous reports of gossypiboma in veterinary medicine, only 4 cases of transmural migration of gossypiboma have been reported. However, none of these cases presented with massive ascites, free gas, or diffuse nodular thickening of the peritoneum. Granulomatous peritonitis is an uncommon postoperative complication that arises from a delayed hypersensitivity reaction to foreign materials. This is the 1st documented case of postoperative granulomatous peritonitis associated with transmural migration of a gossypiboma diagnosed using Computed tomography (CT). Case: A 6-year-old spayed bitch Pompitz that had undergone surgery for pyometra 16 months previously presented with vomiting, diarrhoea, and anorexia. Radiography and ultrasound revealed an abdominal mass, dilated small-intestinal loops, free gas, echogenic ascites, and severe peritonitis. Additionally, a linear foreign body was identified within the jejunum, and a mass with the same echogenicity was found around the expanded intestinal segment. CT showed a classic spongiform pattern in the mass, which continued within the jejunum. A concurrent diffuse nodular pattern and thickening of the peritoneum were also observed. Surgery was performed, and foreign bodies made completely of gauze were found inside the mass and within the jejunal lumen. Ascitic fluid analysis revealed numerous neutrophils, some of which were phagocytosed cocci and bacilli, and a large number of bacteria. Histopathological examination confirmed the presence of pyogranulomatous inflammation. Considering the surgical history and the overall examination results, the occurrence of postoperative granulomatous peritonitis alongside the transmural migration of gossypiboma into the jejunum was strongly suspected, rather than other differential diagnoses such as tuberculous peritonitis or peritoneal carcinomatosis. The bitch was hospitalised in the intensive care unit. She recovered uneventfully, and diffuse nodular thickening of the peritoneum observed on the CT was found to be resolved on ultrasonography performed 5 months after surgery. Discussion: This report describes an atypical case of transmural migration of gossypiboma and postoperative granulomatous peritonitis. Both conditions are primarily diagnosed through clinical signs, history, and diagnostic imaging (radiography, ultrasonography, and CT). Since the clinical signs are nonspecific, diagnostic imaging becomes crucial. Radiography is nonspecific for diagnosis of gossypiboma and often reveals a soft tissue mass with localized gas lucency that appears whirl-like or speckled. The ultrasonographic appearance of gossypibomas can vary based on the foreign body reaction and the gossypiboma's location. CT is a sensitive method for diagnosing gossypiboma, showing a characteristic spongiform pattern. Granulomatous peritonitis is typically associated with infections, malignancies, or idiopathic inflammation, though it can rarely result from foreign material contamination during surgery. In human medicine, CT showed diffuse peritoneal thickening and omental caking, which spontaneously resolved after surgery, as the same was observed in this case. When an animal with a history of surgery showed a spongiform pattern along with diffuse nodular thickening of the peritoneum on CT, this rare condition should be considered as a differential diagnosis. Keywords: CT, dog, canine, gossypiboma, postoperative granulomatous peritonitis, transmural migration.